2016
DOI: 10.5348/ijbti-2016-24-oa-4
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey of human T cell lymphotropic virus I/II among blood donors in Gombe (Nigeria)

Abstract: Aim: this study was carried out to determine the prevalence of human t cell lymphotropic virus I/II (HtLV I/II) among blood donors at the Federal teaching Hospital Gombe (FtHG), North-eastern, Nigeria. Methods: A total of 355

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Okoye et al 1,6 showed prevalence rates of 0.5% and 0%, respectively, in South-East. Zero prevalence has also been reported previously in Nigeria 11 and cases of dual infection with both HTLV-1 and -2 have also been reported in Nigeria. 4 There are limited data on HTLV-2 in Nigeria as compared to its Type 1 counterpart.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Okoye et al 1,6 showed prevalence rates of 0.5% and 0%, respectively, in South-East. Zero prevalence has also been reported previously in Nigeria 11 and cases of dual infection with both HTLV-1 and -2 have also been reported in Nigeria. 4 There are limited data on HTLV-2 in Nigeria as compared to its Type 1 counterpart.…”
Section: Introductionsupporting
confidence: 68%
“…The zero prevalence obtained from this study is similar to those obtained from a different region of the country. 11 Zero prevalence rates have also been reported in other parts of Africa like Mali and Benin Republic. 20,21…”
Section: Discussionmentioning
confidence: 93%